Effectiveness of Implementing Clinical Scaffolding in Mathematics Learning for Elementary School Students - Syarifuddin Syarifuddin; Nurjannah Nurjannah; Nursalim Nursalim; Latri latri (Universitas Islam Ahmad dahlan, 2026)
Mathematics is a subject that is a frightening specter for students. Mathematics is considered a difficult science to understand that requires early handling because it will affect the next academic career level. The purpose of this study was to determine the effectiveness of clinical scaffolding in mathematics learning for elementary school students. This study was an experimental study with a quantitative approach. The subjects of this study were 19 fifth-grade students of SDN 2 Balangnipa. Data collection techniques used observation sheets and mathematical concept understanding tests. Data analysis used descriptive statistical analysis to determine the effectiveness criteria. The results showed that there was an increase in students' mathematical concept understanding ability tests after the implementation of clinical scaffolding, namely the n-gain value was in the high category, and student activity in learning through clinical scaffolding met the ideal time percentage. Based on these results, it can be seen that learning with clinical scaffolding is effectively applied in mathematics learning for elementary school students.